Maternal and Child Mortality: Problems and Solutions in Modern Medicine (Texas Journal of Medical Science, 2025)
Maternal and child mortality is one of the most important problems of modern medicine. This article analyzes the causes of perinatal and maternal mortality, epidemiological data, risk factors and preventive measures. The results of the study show that in order to reduce maternal and child mortality, it is necessary to take into account a comprehensive approach, high-quality antenatal care, qualified medical care and socio-economic factors. The article presents global and regional statistical data, examples from clinical studies, and modern prevention strategies